[Rezension von: Huffman, Douglas S., 1961-, Understanding the New Testament use of the Old Testament : forms, features, framings, and functions] - Allen, David M. (The journal of theological studies, 2025)
Recent decades have seen a number of publications engaging with the way(s) in which the New Testament authors use the Old Testament, and scholarly engageme